The ISTH Bleeding Assessment Tool and the risk of future bleeding. (23rd November 2017) - Fasulo, M. R.; Biguzzi, E.; Abbattista, M.; Stufano, F.; Pagliari, M. T.; Mancini, I.; Gorski, M. M.; Cannavò, A.; Corgiolu, M.; Peyvandi, F.; Rosendaal, F. R.
Abstract : Essentials ISTH Bleeding Assessment Tool (ISTH‐BAT) is used to assist the diagnosis of bleeding disorders. We examined whether the ISTH‐BAT is capable of predicting the risk of future bleeding. 136 subjects were administered the ISTH‐BAT and followed for up to four years. The ISTH‐BAT score failed to predict the risk of future bleeding. Summary: Background: The ISTH Bleeding Assessment Tool (ISTH‐BAT) is a diagnostic tool used in subjects with suspected inherited bleeding disorders. Aim: To evaluate whether the ISTH‐BAT, applied at first work‐up in a tertiary‐care center, predicts the risk of subsequent bleeding events. Methods: This was an observational cohort study including all consecutive subjects, of either sex and any age, referred between 2011 and 2015 because of a suspected bleeding disorder. The analysis was restricted to those with an ISTH‐BAT score of ≥ 3. Incidence rates (IRs) of major bleeding (MB) and clinically relevant non‐major bleeding (CRNMB) events were calculated as the number of events over accrued person‐years. The main analysis was performed with Cox regression analysis, assessing an ISTH‐BAT score of ≤ 5 versus a score of > 5, as well as the score as a continuous variable, and various covariates (sex, age, and presence/absence of a final diagnosis). Results: One hundred and thirty‐six subjects had a median ISTH‐BAT score of 4 (range 3–18). Eleven subjects (8.1%) had a bleeding event during follow‐up (one MB event; 10 CRNMB events). The overall IR of bleeding events per 100 person‐years was 3.7 (95% confidence interval [CI] 1.8–6.6). No difference was observed between subjects with an ISTH‐BAT score of ≤ 5 and those with a score of > 5 (hazard ratio [HR] 1.2, 95% CI 0.3–4.6). The results were similar when the ISTH‐BAT score was considered as a continuous variable (HR 1.1, 95% CI 0.9–1.4). The IR of bleeding was increased in individuals with a diagnosis of a hemostatic defect (IR of 7.5 per 100 person‐years; HR 3.0, 95% CI 0.8–11.8). Conclusions: The ISTH‐BAT does not identify patients at increased risk of future bleeding events.